2015
DOI: 10.1007/s12035-015-9176-4
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention by Regular Exercise of Acute Sleep Deprivation-Induced Impairment of Late Phase LTP and Related Signaling Molecules in the Dentate Gyrus

Abstract: The dentate gyrus (DG) and CA1 regions of the hippocampus are intimately related physically and functionally, yet they react differently to insults. The purpose of this study was to determine the protective effects of regular treadmill exercise on late phase long-term potentiation (L-LTP) and its signaling cascade in the DG region of the hippocampus of rapid eye movement (REM) sleep-deprived rats. Adult Wistar rats ran on treadmills for 4 weeks then were acutely sleep deprived for 24 h using the modified multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…It has been reported that, of the various forms of synaptic plasticity, SD inhibits the induction of hippocampal long-term potentiation, a neural substrate of learning and memory (22). In particular, SD has been identified to impair late-phase long-term potentiation (23,24), which correlates with long-term memory and requires the de novo synthesis of proteins (25)(26)(27).…”
mentioning
confidence: 99%
“…It has been reported that, of the various forms of synaptic plasticity, SD inhibits the induction of hippocampal long-term potentiation, a neural substrate of learning and memory (22). In particular, SD has been identified to impair late-phase long-term potentiation (23,24), which correlates with long-term memory and requires the de novo synthesis of proteins (25)(26)(27).…”
mentioning
confidence: 99%
“…24-h sleep deprivation was induced by putting the animals in an 8 circular small platforms aquarium (125 × 44 × 44 cm and 6.5 cm in diameter) has been explained before (Parsa et al 2016;Zagaar et al 2016). The EEG recording confirmed the induction of sleep deprivation by multiple plate forms model (Arthaud et al 2015).…”
Section: Acute Sleep Deprivation Inductionmentioning
confidence: 68%
“…The non-significant effect of extended sleep on hippocampal IGF-I levels supported previous results showing that sleep quality and sleep quantity in non-stressed animals showed predictive changes in translational factor activity in cortical but not hippocampal regions [ 39 ]. The absence of effect may also be due to IGF-I measurement in whole hippocampal tissue—not specific areas dedicated to learning and short-term memory—and synaptic plasticity such as CA1 or dentate gyrus [ 40 ]. In our study, additional sleep time induced higher circulating and muscle IGF-I levels, and higher weight gain was positively correlated with them, and these results shed light on the anabolic properties of sleep [ 33 ].…”
Section: Discussionmentioning
confidence: 99%